In vitro tissue culture in plants propagation and germplasm conservation of economically important species in Peru (Scientia Agropecuaria, 2021)
Plant biotechnology is one of the most important tools presently available and methods to genetically manipulate plants to exhibit greater productivity, tolerance to physical and chemical stress, and resistance to pests and diseases have been developed in recent decades. In vitro plant tissue culture has contributed significantly to this purpose. The objective of this study is to apply various techniques developed by in vitro tissue culture in seed germination, meristem culture for virus elimination, micropropagation, conservation, international transfer of germplasm, and induction of various morphogenic processes that lead to the genetic variability known as somaclonal variation. The application of this set of biotechnological techniques, in crops such as cassava, sweet potato, potato, native forest species as Cedrela odorata, Ficus spp. Loxopterygium huasango, and others, sugar cane, rice, pineapple, among other haves made it possible to meet, as a matter of improvement, several of the essential needs of farmers in the region of northern Peru. The development of these technologies will allow their wide application not only in the propagation, genetic improvement and conservation of species of economic importance, food and medicine, but also in the forest species of the seasonally dry tropical forest of northern Peru.